Cfd simulation of multiple array arrangement of micro hydro power turbines - Thiwaan Rao, Narasimma Naidu (2013)
Micro Hydro Power (MHP) turbines were used to generate energy with a water flow. This energy is useful to the mankind. Computational Fluid Dynamics (CFD) software was used to simulate the water flow over MHP turbines as they are placed in a river domain. Multiple arrays arrangement of MHP turbines lead to generate large amount of energy. It is rare to find CFD simulation of MHP turbines. In this study, a river model was created and simulated in CFD software to obtain the water flow characteristic over MHP turbine bodies. The process then continued by simulating different types of arrays arrangement in the river model. A MHP turbine model consists of a turbine outer body and static propeller blade in it. Five types of different array arrangements were used which are parallel, series, triangular, square and rhombus with different spacing sizes. The velocity profiles on each MHP turbines were identified at the mouth of turbine body. In this study, the triangular, square and rhombus arrangements were significant to generate power because their average velocities increase as the spacing sizes increase but parallel and series arrangements were not significant.